DIETARY EXPOSURE TO ANTIMICROBIAL RESISTANCE GENES (ARGs) FROM LIVESTOCK PRODUCTS AND ITS IMPLICATIONS FOR GUT HEALTH IN CHILDREN – A REVIEW - Euodia Sinthika; Ninik Rustanti; Endang Sri Lestari (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2026)
ABSTRACTBackground: ARGs found in animal-derived foods represent a significant route of antimicrobial resistance transmission beyond clinical antibiotic use. Livestock products such as meat, milk, eggs, and fish from animals exposed to antibiotics frequently contain diverse ARGs. Because the gut microbiota of infants and young children is still forming, dietary exposure to ARGs may have amplified biological effects during early development.Objective: This review aims to synthesize current evidence the presence of ARGs in livestock-based foods, evaluates how dietary intake may contribute to ARG exposure in children, and describes the mechanisms through which these genes may influence gut microbiota development and child health.Methods: A comprehensive literature search were conducted in PubMed, MEDLINE, Web of Science, and Google Scholar. English-language studies involving human or animal subjects were included if they examined ARGs in animal-source foods or their implications for gut microbiota and pediatric health. Findings from cohort studies, randomized controlled trials, and mechanistic research were integrated narratively.Results: Studies report ARGs such as blaCTX-M, mecA, tetM, sul1, and gyrA in poultry, beef, milk, eggs, and fish. Following ingestion, ARGs may interact with the pediatric gut through horizontal gene transfer—via conjugation, transformation, or transduction—promoting dysbiosis, increasing susceptibility to infection, reducing antibiotic effectiveness, and influencing immune function during early life.Conclusion: Dietary exposure to ARGs from animal-source foods may contribute to early establishment of the gut resistome in children and alter microbiota-related functions. Strengthened control of ARGs along the food production chain is essential to reduce exposure and protect child health.Keywords: Antimicrobial Resistance Genes (ARGs); gut microbiota; diet; children